LATE JURASSIC AND EARLY CRETACEOUS AMMONITES FROM THE WEIMEI FORMATION IN GYANGZE, SOUTHERN TIBET (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Weimei Formation in southern Tibet is a shallow marine sequence accumulated in the northern margin of the Indian subcontinent. It has been dated as Tithonian based on ammonites such as Haplophylloceras strigile (Blanford), Berriasella sp. and Himalayites sp. Six ammonite specimens were found in the type locality of the Weimei Formation. They include Spiticeras (Spiticeras) spitiense (Blanford), Berriasella sp. and Phylloceras sp. The occurrence of S. spitiense indicates that the ammonite-bearing portion is assignable to the Berriasian stage. The Jurassic/Cretaceous boundary possibly exists within the Weimei Formation.